Resmetirom for Metabolic Dysfunction-Associated Steatohepatitis: Systematic Review with Meta-Analysis - Araújo Soares, Windson Hebert; Soares Motta Santos, André (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objectives: To evaluate the evidence on the efficacy, safety, and cost-effectiveness of res-metirom for metabolic dysfunction-associated steatohepatitis (MASH). Methods: A syste-matic review with meta-analysis of randomized clinical trials was conducted, comparing resmetirom to placebo or active comparators for the treatment of MASH (PROSPERO: CRD42024557306). Searches were performed in 06/2024 in the Medline, Embase, Lilacs, Cochrane, and Centre for Reviews and Dissemination databases. Two researchers independently selected studies, extracted data, and assessed their methodological quality. Meta-analyses were conducted in R. The risk of bias in randomized clinical trials was assessed using the Cochrane Collaboration’s RoB-2 tool, and the level of evidence was evaluated using the GRADE approach. Results: The final sample was composed by eight publications. Resmetirom was shown to be effective in resolving MASH, with a 149% improvement compared to the control group. It also significantly improved liver fibrosis and reduced liver fat, with notable effects in long-term studies. However, an increased incidence of diarrhea and nausea was observed among treated patients. Laboratory parameters, such as LDL and triglycerides, also improved with resmetirom. The technolo-gy was considered cost-effective at a threshold of $100,000/QALY (ICER ranging from $36,600/QALY to $74,018/QALY) in studies worldwide. Conclusion: Resmetirom demonstrated significant and sustained reductions in liver fat and improvements in fibrosis, proving to be effective, safe, and potentially cost-effective for the treatment of MASH.